P365 Biological interventions for induction and maintenance of mucosal healing in Crohn's disease: A Cochrane systematic review. (16th January 2018) - Ricciuto, A; Church, P; Stewart, M J; Shim, H H; Storr, M; Panaccione, R; Griffiths, A; Seow, C
Abstract: Background: Clinical trials of biologics in Crohn's disease (CD) have focused on clinical outcomes. Their ability to achieve mucosal healing (MH) is less clear. In this Cochrane review, we synthesised the randomised controlled trial (RCT) data on biologics for inducing and maintaining MH in CD. Methods: MEDLINE, EMBASE, Cochrane Library (CENTRAL) and the Cochrane IBD Group Specialised Trials Register were searched to October 2017 for RCTs examining biologics for inducing and/or maintaining MH in CD at 4–26 and >26 weeks, respectively. Secondary outcomes were endoscopic response (ER), safety and quality of life (QOL). Pooled risk ratios (RR) were calculated using a random-effects model. The quality of the evidence was rated using GRADE. Results: The search yielded 7 induction trials (5 low, 2 unclear risk of bias). Infliximab (IFX) was superior to placebo (PBO) for inducing MH at week 10 (RR 8.4, 95% CI 1.2–61, n = 74, low quality), and IFX mono- and combination therapy with azathioprine (AZA) were superior to AZA for inducing MH at week 26 (RR 1.9, 95% CI 1.1–3.1, n = 218, low quality, and RR 2.7, 95% CI 1.7–4.3, n = 232, moderate quality). MH rates did not differ significantly between adalimumab (ADA) and PBO-treated patients, but ADA users were more likely to achieve CDEIS ≤4 at week 12 (RR 1.9, 95% CI 1.2–3.0, n = 123, low quality). Neither natalizumab (RR 2.8, 95% CI 0.4–20, n = 50, low quality), nor ustekinumab (UST) (RR 2.1, 95% CI 0.81–5.4, n = 302, low quality) was superior to PBO for inducing MH, but UST users displayed significantly greater SES-CD reductions in one study (low quality). The search identified 3 maintenance trials, each examining a different biologic (2 low, one high risk of bias). Neither IFX nor ADA was superior to PBO for maintaining MH achieved during induction, but patient numbers were extremely small. Comparable data were not available for UST. Amongst all randomised patients (regardless of MH status at induction completion), only ADA was associated with higher 1-year MH rates than PBO (RR 30.5, 95% CI 1.9–499, moderate quality for ADA; RR 2.4, 95% CI 0.94–6.4, low quality for IFX; RR 2.2, 95% CI 0.86-5.6, very low quality for UST). All 3 biologics displayed a significant benefit for ER at 1 year. Adverse event rates were similar between groups, but one case of progressive multifocal leukoencephalopathy was observed with natalizumab. IFX and UST were associated with improved QOL. Conclusions: The evidence supports the efficacy of IFX for inducing MH (low-to-moderate quality), and of ADA and UST for inducing ER (low quality), in CD. ADA was associated with higher maintenance MH rates than PBO at 1 year, with ADA, IFX and UST displaying significantly higher rates of ER. There is no RCT evidence for certolizumab or vedolizumab.